ANALISIS KEBANGRUTAN USAHA DENGAN MULTIPLE DISCRIMINANT ANALYSIS / MDA (Z-SCORE) MODEL ALTMAN PERTAMA MENGGUNAKAN MS. ACCESS PROGRAMMING - Suhartono, Suhartono (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2012)
Progress of a company is absolutely necessary in the face of global competition today. In the era of globalization and free market, companies are required to continue developing and developed with a very high competitive level. There are many factors that affect the progress of a company starting from the factor of human resources, financial resources external to the company. None of the companies thatwant their business so that the necessary bangrut planning is good and earnest efforts for the company to move forward and survive. Financial statements is one indicator that can measure whether the company was in good health or not. There are many methods of analysis that can be used to measure the performance of the company. One is the method of Altman Z-score. Altman Z-score is the most famous models in predicting bankruptcy of enterprises. This highly accurate method for measuring whether a company in financial difficulties or not. Because of financial difficulties was the beginning of the bankruptcy business. Altman Z-score model using data from the report noted that financial-data to beprocessed into an accurate data. The model is then combined with MS. Access Programming to produce an application that is fast, precise and accurate in predicting bankruptcy of enterprises.